2017
DOI: 10.1073/pnas.1621161114
|View full text |Cite
|
Sign up to set email alerts
|

RhoA knockout fibroblasts lose tumor-inhibitory capacity in vitro and promote tumor growth in vivo

Abstract: Fibroblasts are a main player in the tumor-inhibitory microenvironment. Upon tumor initiation and progression, fibroblasts can lose their tumor-inhibitory capacity and promote tumor growth. The molecular mechanisms that underlie this switch have not been defined completely. Previously, we identified four proteins overexpressed in cancer-associated fibroblasts and linked to Rho GTPase signaling. Here, we show that knocking out the Ras homolog family member A (RhoA) gene in normal fibroblasts decreased their tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 51 publications
1
32
0
Order By: Relevance
“…In support of this, in lung adenocarcinomas, glycosylated vimentin was shown to be frequently downregulated, defining its potential as a biomarker both for treatment and diagnosis [ 253 ]. A more recent study showed that vimentin expression in cancer-associated fibroblasts is required for dissemination of early stage lung adenocarcinoma, which indicates that vimentin might have a key role in the cancer-promoting capacity of cancer-associated fibroblasts in the tumour microenvironment [ 254 ]. Fibroblasts that promote the growth of cancer cells in vivo have also been shown to have reorganised vimentin filaments, compared to normal fibroblasts [ 255 ].…”
Section: Vimentin: a Drug Target And Biomarker In The Clinicmentioning
confidence: 99%
“…In support of this, in lung adenocarcinomas, glycosylated vimentin was shown to be frequently downregulated, defining its potential as a biomarker both for treatment and diagnosis [ 253 ]. A more recent study showed that vimentin expression in cancer-associated fibroblasts is required for dissemination of early stage lung adenocarcinoma, which indicates that vimentin might have a key role in the cancer-promoting capacity of cancer-associated fibroblasts in the tumour microenvironment [ 254 ]. Fibroblasts that promote the growth of cancer cells in vivo have also been shown to have reorganised vimentin filaments, compared to normal fibroblasts [ 255 ].…”
Section: Vimentin: a Drug Target And Biomarker In The Clinicmentioning
confidence: 99%
“…RhoA is a master regulator of cell shape, adhesiveness, contractile behavior, and the configuration of focal adhesions [ 39 ]. Our studies showed that knockout of the RhoA gene in fibroblasts disturbs cytoskeletal organization, increases cellular stiffness, and decreases cellular contractility [ 40 ], which all are important properties required to maintain normal connective tissue structure and function [ 39 , 40 ]. As a result, the fibroblasts lose their tumor suppressive function and, rather, provide a growth stimulatory niche via induction of a cancer propagating phenotype in 3D-collagen culture and xenograft tumors in vivo [ 40 ].…”
Section: Normal Fibroblasts: the Anti-tumorigenic Responsementioning
confidence: 99%
“…RhoA is present at the cell membrane when it is active [ 84 ]. RhoA regulates the generation of actomyosin bundles, stress fibers, focal adhesions, and lamellipodia [ 85 ]. RhoB is found in endosomes and at the plasma membrane.…”
Section: Rho/rock Signaling In Cytoskeletal Reorganizationmentioning
confidence: 99%